Implementation of the Cooperative Learning Learning Model Type Student Teams Achievement Division in Enhancing Students' Critical Thinking - Putri, Yulianda Melani; Nazmi, Ranti; Juliardi, Budi (Jurnal Pendidikan Amartha, 2023)
This study aims to describe the Implementation of the Student Teams Achievement Division (STAD) Cooperative Learning Learning Model in Improving Students' Critical Thinking in Civics Learning at SMP N 1 Sitiung. The research method used in this research is descriptive qualitative with the research location at SMP N 1 Sitiung. The informants in this study totaled 7 people including 6 students, 1 educator who taught Civics subjects. Data collection was carried out through observation, interviews and documentation techniques, then for data analysis techniques carried out through the stages of data reduction, data presentation and drawing conclusions. The results of this study indicate that the process of implementing the cooperative learning model type Student Teams Achievement Division (STAD) in increasing students' critical thinking in learning PPKn at SMP N 1 Sitiung has been carried out well. This is inseparable from the efforts that have been made by educators. The efforts made by educators in increasing students' critical thinking are by changing the learning model used in the learning process. The cooperative learning model of the Student Teams Achievement Division (STAD) type is an example of a learning model that can improve students' critical thinking. Another effort made by educators to increase students' critical thinking is by creating a fun learning process by providing motivation to students to be more active in learning. Based on the results of this study, it can be concluded that the process of implementing the cooperative learning model of the Student Teams Achievement Division (STAD) type in increasing students' critical thinking in Civics learning at SMP N 1 Sitiung has been carried out well. The efforts that have been made by educators in increasing students' critical thinking are: (a) creating fun learning (b) conducting intensive guidance to groups experiencing difficulties (c) giving rewards to groups that can present the results of discussions well.